Comparative global burden of ischemic heart disease and myocardial disease attributable to non-optimal temperatures, 1990–2021: an analysis based on GBD 2021 - Guo, Mengqi; Lian, Zhexun; Xia, Zongyi; Wang, Lingbing; Xin, Hui; Li, Fuhai (Frontiers in Public Health, 2025)
ObjectivesTo compare the global burden of myocardial disease (MD) and ischemic heart disease (IHD) attributable to high and low temperatures, and to examine demographic and socio-economic disparities over time.MethodsWe analyzed disability-adjusted life years (DALYs) and mortality for MD and IHD attributable to high and low temperatures, stratified by sex, age, region, and socio-demographic index (SDI). Decomposition analysis quantified the contributions of population growth, aging, and epidemiological changes. Projections were generated using an age-period-cohort model.ResultsBetween 1990 and 2021, high temperature-related MD and IHD burdens increased [Estimated Annual Percent Change (EAPC): +1.26 and +1.68%, respectively], whereas low temperature burdens declined (EAPC: −1.87 and −1.73%) but remained considerably higher overall. MD disproportionately affected children under five and adults over 80, while IHD rarely appeared under 30 yet rose markedly from midlife onward. Heat-related MD and IHD burdens rose with SDI < 0.5 and declined above 0.5; cold-related burdens decreased consistently above SDI 0.75 but varied irregularly below this threshold. Central Asia exhibited the greatest heat- and cold-related burdens for both MD and IHD, whereas North Africa and the Middle East were particularly susceptible to heat. Population growth primarily fueled heat-related burdens, whereas cold-related burdens were more driven by aging and population change. Projections to 2040 indicate continuing increases in heat-related burdens, potentially exacerbating health disparities.ConclusionsHeat-attributable IHD is the fastest-growing threat, while MD remains critical for very young and older adult populations under extreme temperatures. Disparities across age, SDI, and geography highlight the urgency for targeted interventions.